Applications of near-infrared spectroscopy in “anaerobic” diagnostics – SmO2 kinetics reflect PCr dephosphorylation and correlate with maximal lactate accumulation and maximal pedalling rate - Dunst, Anna; Manunzio, Christian; Feldmann, Andri; Hesse, Clemens (Biology of Sport, 2023)
We investigated the relationship of the time-dependent behaviour of muscle oxygen saturation SmO 2 (t), phosphagen energy supply W PCr (t) and blood lactate accumulation ΔBLC(t) during a 60-s all-out cycling sprint and tested SmO 2 (t) for correlations with the end of the fatigue-free state t Ff , maximal pedalling rate PR max and maximal blood lactate accumulation rate v̇La max . Nine male elite track cyclists performed four maximal sprints (3, 8, 12, 60 s) on a cycle ergometer. Crank force and cadence were monitored continuously to determine PR max and t Ff based on force-velocity profiles. SmO 2 of the vastus lateralis muscle and respiratory gases were measured until the 30th minute after exercise. W PCr was calculated based on the fast component of the post-exercise oxygen uptake for each sprint. Before and for 30 minutes after each sprint, capillary blood samples were taken to determine the associated ΔBLC. Temporal changes of SmO 2 , W PCr and ΔBLC were analysed via non-linear regression analysis. v̇La max was calculated based on ΔBLC(t) as the highest blood lactate accumulation rate. All models showed excellent quality (R 2 > 0.95). The time constant of SmO 2 (t) τSmO 2 = 2.93±0.65 s was correlated with the time constant of WPCr(t) τ PCr = 3.23±0.67 s (r = 0.790, p < 0.012), v̇La ma x = 0.95±0.18 mmol·l −1 ·s −1 (r = 0.768, p < 0.017) and PR max = 299.51±14.70 rpm (r = -0.670, p < 0.049). t Ff was correlated with τ SmO2 (r = 0.885, p < 0.001). Our results show a time-dependent reflection of SmO 2 kinetics and phosphagen energy contribution during a 60-s maximal cycling sprint. A high v̇La max results in a reduction, a high PR max in an increase of the desaturation rate. The half-life of SmO 2 desaturation indicates the end of the fatigue-free state.